Multidimensional conductive network sodium ion battery negative electrode material and preparation method and application thereof

By adopting a multi-dimensional conductive network structure and doping 2,5-diphenyl-1,4benzenequinone in the negative electrode material of sodium ion battery, the problem of insufficient conductivity and redox potential of the negative electrode material of sodium ion battery is solved, and the cyclic stability of the material is significantly improved, laying the foundation for the development of high-capacity sodium ion battery.

CN119627101BActive Publication Date: 2025-05-02ZIBO TORCH ENERGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510153107.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-05-02
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

The negative electrode material of sodium ion batteries performs poorly in terms of conductivity and redox potential, and is prone to powder during charging and discharging, affecting the cycling performance and rate performance.

Method used

A sodium ion battery negative electrode material with a multi-dimensional conductive network structure was prepared by mixing red phosphorus with MnSn2 and dry ball milling, sintering and hydrothermal reaction, doping 2,5-diphenyl-1,4 benzenequinone to prepare an anode material with high conductivity and redox potential.

Benefits of technology

It significantly improves the conductivity and redox potential of the material, suppresses the powdering phenomenon, improves cycle stability, and provides a basis for the development of high-capacity and long cycle life sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium batteries, and specifically relates to a multidimensional conductive network sodium ion battery negative electrode material, a preparation method and an application thereof. The preparation method comprises: (1) mixing red phosphorus and MnSn2, and performing dry ball milling under vacuum conditions to obtain a mixed powder A; (2) placing the mixed powder A in a tubular furnace under an argon atmosphere for sintering to obtain a mixed powder B; (3) placing the mixed powder B in a hydrothermal kettle, adding 2,5-diphenyl-1,4-benzoquinone and ethanol, and performing a hydrothermal reaction; (4) placing the mixed powder B in a vacuum drying oven after the hydrothermal reaction for drying, and after drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained. The material significantly improves the conductivity and redox potential, and effectively suppresses the pulverization phenomenon of the material during the charge and discharge process, thereby greatly improving the cycle stability of the material, and laying an important foundation for the development of high-capacity and long cycle life sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium batteries, and in particular relates to a multi-dimensional conductive network sodium ion battery negative electrode material and a preparation method and application thereof. Background Art

[0002] As a new battery technology, sodium-ion batteries have received widespread attention in recent years. Compared with lithium-ion batteries, sodium-ion batteries have higher safety, lower costs, and more abundant resource reserves. The abundance of sodium in the earth's crust is much higher than that of lithium, which gives sodium-ion batteries a significant cost advantage in large-scale energy storage applications. In addition, sodium-ion batteries are also safer than lithium-ion batteries under extreme conditions such as high temperature and overcharging, which provides potential advantages for their application in fields such as electric vehicles and grid energy storage.

[0003] However, the development of sodium-ion batteries still faces some technical challenges. Compared with lithium-ion batteries, the negative electrode materials of sodium-ion batteries perform poorly in terms of conductivity and redox potential. The large ionic radius of sodium ions makes it difficult to embed and de-embed the electrode materials, which affects the battery's cycle performance and rate performance. In addition, the range of negative electrode materials for sodium-ion batteries is narrow, and the existing material system still needs to be improved in terms of capacity utilization and cycle stability. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a multi-dimensional conductive network sodium ion battery negative electrode material, which significantly improves the conductivity and redox potential, and effectively inhibits the pulverization of the material during the charge and discharge process, thereby greatly improving the cycle stability of the material, laying an important foundation for the development of high-capacity and long cycle life sodium ion batteries, and has broad application prospects.

[0005] Another object of the present invention is to provide a preparation method and application of a multi-dimensional conductive network sodium ion battery negative electrode material.

[0006] The technical solution adopted by the present invention is as follows:

[0007] The method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material comprises the following steps:

[0008] (1) After mixing red phosphorus and MnSn2, dry ball milling was performed under vacuum conditions. The speed of dry ball milling was 200 rpm and the time of dry ball milling was 6 h. After dry ball milling, mixed powder A was obtained;

[0009] (2) In an argon atmosphere, the mixed powder A is placed in a tube furnace and sintered by a high-temperature solid phase method. After sintering, the mixed powder is naturally cooled to room temperature to obtain a mixed powder B;

[0010] (3) Putting the mixed powder B into a hydrothermal reactor, adding 2,5-diphenyl-1,4-benzoquinone and ethanol, and carrying out a hydrothermal reaction;

[0011] (4) The material obtained after the hydrothermal reaction is naturally cooled to room temperature and then placed in a vacuum drying oven for drying. After drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained.

[0012] In the step (1), the mass ratio of red phosphorus to MnSn2 is 10:(1-2).

[0013] In the step (1), a planetary ball mill is used for dry ball milling, and agate balls are used as grinding balls.

[0014] In the step (1), the ball-to-material ratio of dry ball milling is (8-10):1.

[0015] In the step (2), the sintering temperature is 350-400°C, the sintering time is 8-10h, and the heating rate is 1-3°C / min.

[0016] In the step (3), the mass ratio of the mixed powder B to 2,5-diphenyl-1,4-benzoquinone is 40:(1-2).

[0017] In the step (3), the mass volume ratio of the total amount of the mixed powder B and 2,5-diphenyl-1,4-benzoquinone added to the amount of ethanol added is (4-6): 20 mg / mL.

[0018] In the step (3), the temperature of the hydrothermal reaction is 450-500°C, the time of the hydrothermal reaction is 3-5h, and the heating rate is 1-3°C / min.

[0019] In the step (4), the drying temperature is 90-120° C. and the drying time is 8-12 hours.

[0020] The multi-dimensional conductive network sodium ion battery negative electrode material is prepared by the above-mentioned method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material.

[0021] The multi-dimensional conductive network sodium ion battery negative electrode material is used to prepare a sodium ion battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The method for preparing the multidimensional conductive network sodium ion battery negative electrode material of the present invention has simple process, safety, environmental protection and low cost. The method uses red phosphorus and tin-manganese alloy to react to generate metal phosphide, and simultaneously dopes quinone organic compounds to prepare the multidimensional conductive network sodium ion battery negative electrode material, effectively improves the conductivity and redox potential of the material, and inhibits the pulverization phenomenon of the material during the charge and discharge process, significantly improves the cycle stability of the material, and provides a basis for further preparing high-capacity sodium ion batteries, and has broad application prospects. DETAILED DESCRIPTION

[0024] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.

[0025] Unless otherwise specified, the raw materials used in the examples and comparative examples are conventional commercially available raw materials, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.

[0026] Some of the raw materials used in the examples and comparative examples are described as follows:

[0027] MnSn2 was purchased from Tangshan Kailai New Materials Co., Ltd.

[0028] Example 1

[0029] The method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material comprises the following steps:

[0030] (1) After mixing red phosphorus and MnSn2 in a mass ratio of 10:1, dry ball milling was performed in a planetary ball mill under vacuum conditions, using agate balls as grinding balls, the speed of dry ball milling was 200 rpm, the dry ball milling time was 6 h, the ball-to-material ratio was 8:1, and mixed powder A was obtained after dry ball milling;

[0031] (2) In an argon atmosphere, the mixed powder A was placed in a tubular furnace and sintered by a high-temperature solid phase method. The sintering temperature was 350°C, the sintering time was 8 h, the heating rate was 1°C / min, and after sintering, it was naturally cooled to room temperature to obtain a mixed powder B;

[0032] (3) The mixed powder B was placed in a hydrothermal reactor, and 2,5-diphenyl-1,4-benzoquinone and ethanol were added to carry out a hydrothermal reaction. The temperature of the hydrothermal reaction was 450°C, the time of the hydrothermal reaction was 3 hours, and the heating rate was 1°C / min. The mass ratio of the mixed powder B to 2,5-diphenyl-1,4-benzoquinone was 40:1.5. The mass volume ratio of the total amount of the mixed powder B and 2,5-diphenyl-1,4-benzoquinone added to the amount of ethanol added was 4:20 mg / mL.

[0033] (4) The material obtained after the hydrothermal reaction is naturally cooled to room temperature, and then placed in a vacuum drying oven for drying at a temperature of 90° C. and a drying time of 8 h. After drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained.

[0034] Example 2

[0035] The method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material comprises the following steps:

[0036] (1) After mixing red phosphorus and MnSn2 in a mass ratio of 10:1.5, dry ball milling was performed in a planetary ball mill under vacuum conditions, using agate balls as grinding balls, the speed of dry ball milling was 200 rpm, the dry ball milling time was 7 h, the ball-to-material ratio was 9:1, and mixed powder A was obtained after dry ball milling;

[0037] (2) In an argon atmosphere, the mixed powder A was placed in a tube furnace and sintered by a high-temperature solid phase method. The sintering temperature was 380°C, the sintering time was 9 hours, the heating rate was 2°C / min, and after sintering, it was naturally cooled to room temperature to obtain a mixed powder B;

[0038] (3) The mixed powder B was placed in a hydrothermal reactor, and 2,5-diphenyl-1,4-benzoquinone and ethanol were added to carry out a hydrothermal reaction. The temperature of the hydrothermal reaction was 480°C, the time of the hydrothermal reaction was 4 hours, and the heating rate was 2°C / min. The mass ratio of the mixed powder B to 2,5-diphenyl-1,4-benzoquinone was 40:1. The mass volume ratio of the total amount of the mixed powder B and 2,5-diphenyl-1,4-benzoquinone added to the amount of ethanol added was 5:20 mg / mL.

[0039] (4) The material obtained after the hydrothermal reaction is naturally cooled to room temperature and then placed in a vacuum drying oven for drying at a temperature of 100° C. for a drying time of 9 h. After drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained.

[0040] Example 3

[0041] The method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material comprises the following steps:

[0042] (1) After mixing red phosphorus and MnSn2 in a mass ratio of 10:2, dry ball milling was performed in a planetary ball mill under vacuum conditions, using agate balls as grinding balls, the speed of dry ball milling was 250 rpm, the dry ball milling time was 8 h, the ball-to-material ratio was 10:1, and mixed powder A was obtained after dry ball milling;

[0043] (2) In an argon atmosphere, the mixed powder A was placed in a tube furnace and sintered by a high-temperature solid phase method at a sintering temperature of 400°C, a sintering time of 10 h, a heating rate of 3°C / min, and naturally cooled to room temperature after sintering to obtain a mixed powder B;

[0044] (3) The mixed powder B was placed in a hydrothermal reactor, and 2,5-diphenyl-1,4-benzoquinone and ethanol were added to carry out a hydrothermal reaction. The temperature of the hydrothermal reaction was 500°C, the time of the hydrothermal reaction was 5 hours, and the heating rate was 3°C / min. The mass ratio of the mixed powder B to 2,5-diphenyl-1,4-benzoquinone was 40:2. The mass volume ratio of the total amount of the mixed powder B and 2,5-diphenyl-1,4-benzoquinone added to the amount of ethanol added was 6:20 mg / mL.

[0045] (4) The material obtained after the hydrothermal reaction is naturally cooled to room temperature, and then placed in a vacuum drying oven for drying at a temperature of 110° C. for a drying time of 10 h. After drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained.

[0046] Example 4

[0047] The method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material comprises the following steps:

[0048] (1) After mixing red phosphorus and MnSn2 in a mass ratio of 10:1, dry ball milling was performed in a planetary ball mill under vacuum conditions, using agate balls as grinding balls, the speed of dry ball milling was 300 rpm, the dry ball milling time was 6 h, the ball-to-material ratio was 9:1, and mixed powder A was obtained after dry ball milling;

[0049] (2) In an argon atmosphere, the mixed powder A was placed in a tube furnace and sintered by a high-temperature solid phase method. The sintering temperature was 350°C, the sintering time was 10 h, the heating rate was 1°C / min, and after sintering, it was naturally cooled to room temperature to obtain a mixed powder B;

[0050] (3) The mixed powder B was placed in a hydrothermal reactor, and 2,5-diphenyl-1,4-benzoquinone and ethanol were added to carry out a hydrothermal reaction. The temperature of the hydrothermal reaction was 450°C, the time of the hydrothermal reaction was 4 hours, and the heating rate was 2°C / min. The mass ratio of the mixed powder B to 2,5-diphenyl-1,4-benzoquinone was 40:1. The mass volume ratio of the total amount of the mixed powder B and 2,5-diphenyl-1,4-benzoquinone added to the amount of ethanol added was 4:20 mg / mL.

[0051] (4) The material obtained after the hydrothermal reaction is naturally cooled to room temperature, and then placed in a vacuum drying oven for drying at a temperature of 120° C. for a drying time of 12 h. After drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained.

[0052] Example 5

[0053] The method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material comprises the following steps:

[0054] (1) After mixing red phosphorus and MnSn2 in a mass ratio of 10:1.5, dry ball milling was performed in a planetary ball mill under vacuum conditions, using agate balls as grinding balls, the speed of dry ball milling was 280 rpm, the dry ball milling time was 8 h, the ball-to-material ratio was 8:1, and mixed powder A was obtained after dry ball milling;

[0055] (2) In an argon atmosphere, the mixed powder A was placed in a tube furnace and sintered by a high-temperature solid phase method. The sintering temperature was 380°C, the sintering time was 9 hours, the heating rate was 3°C / min, and after sintering, it was naturally cooled to room temperature to obtain a mixed powder B;

[0056] (3) The mixed powder B was placed in a hydrothermal reactor, and 2,5-diphenyl-1,4-benzoquinone and ethanol were added to carry out a hydrothermal reaction. The temperature of the hydrothermal reaction was 500°C, the time of the hydrothermal reaction was 3 h, and the heating rate was 1°C / min. The mass ratio of the mixed powder B to 2,5-diphenyl-1,4-benzoquinone was 40:2. The mass volume ratio of the total amount of the mixed powder B and 2,5-diphenyl-1,4-benzoquinone added to the amount of ethanol added was 6:20 mg / mL.

[0057] (4) The material obtained after the hydrothermal reaction is naturally cooled to room temperature and then placed in a vacuum drying oven for drying at a temperature of 100°C for a time of 12 hours. After drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained.

[0058] Comparative Example 1

[0059] The difference from Example 1 is that MnSn2 is not added in step (1).

[0060] Comparative Example 2

[0061] The difference from Example 2 is that 2,5-diphenyl-1,4-benzoquinone is not added in step (3).

[0062] Comparative Example 3

[0063] The difference from Example 3 is that in step (1), the rotation speed of the dry ball milling is 150 rpm and the time of the dry ball milling is 3 h.

[0064] Comparative Example 4

[0065] The difference from Example 4 is that MnSn2 is not added in step (1) and 2,5-diphenyl-1,4-benzoquinone is not added in step (3).

[0066] The negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-4 were respectively used to assemble full batteries. The specific battery assembly process is as follows:

[0067] Sodium nickel iron manganese oxide was used as the positive electrode, and the negative electrode materials prepared in Examples 1-5 and Comparative Examples 1-4 were used as the negative electrode to prepare 96mm×81mm positive electrode sheets and 98mm×83mm negative electrode sheets, respectively; NaPF6 was used as the solute and a mixture of EC, DMC and DEC in a volume ratio of 1:1:1 was used as the solvent to prepare a NaPF6 solution with a concentration of 1 mol / L as the electrolyte; a soft-pack sodium ion battery was assembled using a ceramic diaphragm with an NP ratio of 1.1:1; the assembled full battery was subjected to charge and discharge tests and cycle performance tests, respectively, with a current density of 0.33C.

[0068] The measured initial discharge capacity (mAh) and capacity retention rate (%) after 30 cycles are shown in Table 1.

[0069] Table 1 Performance test results

[0070]

[0071] It can be seen from the data in Table 1 that after the negative electrode materials prepared in Examples 1-5 are used to assemble the battery, the initial discharge capacity and the capacity retention rate after 30 cycles of the battery are better than those of the comparative example.

[0072] Compared with Example 1, since no MnSn2 is added in Comparative Example 1, the battery interface charge transfer resistance is higher, and the phosphorus-based material is easily pulverized, which further affects the conductivity and cycle performance of the battery.

[0073] Compared with Example 2, since no 2,5-diphenyl-1,4-benzoquinone was added in Comparative Example 2, the initial discharge capacity and the capacity retention rate after 30 cycles of the battery assembled using the negative electrode material prepared in Comparative Example 2 were lower than those in Example 2. This is because 2,5-diphenyl-1,4-benzoquinone contains two carbonyl groups, and this unique network chemical structure has a higher redox potential and multi-electron reaction ability, so that the negative electrode material in Example 2 exhibits higher discharge capacity and better cycle performance.

[0074] Compared with Example 3, in Comparative Example 3, due to insufficient ball milling speed and short ball milling time, the solid mixing is insufficient, the grinding is uneven, and the particle size of the mixture is large, which is not conducive to the electrochemical reaction. Therefore, the first discharge capacity and the capacity retention rate after 30 cycles of the battery assembled using the negative electrode material prepared in Comparative Example 3 are lower than those in Example 3.

[0075] Compared with Example 4, since MnSn2 and 2,5-diphenyl-1,4-benzoquinone were not added in Comparative Example 4, the battery assembled with the negative electrode material prepared therefrom showed lower initial discharge capacity and capacity retention after 30 cycles. This is because both MnSn2 and 2,5-diphenyl-1,4-benzoquinone have the characteristics of improving conductivity, and their doping can effectively improve the conductivity of phosphorus-based compounds and increase the redox potential. These improvements are conducive to the smooth progress of the electrochemical process, thereby showing higher discharge capacity and excellent cycle performance.

Claims

1. A method for preparing a multidimensional conductive network sodium ion battery negative electrode material, characterized in that: The following steps are involved: (1) After mixing red phosphorus and MnSn2, dry ball milling was performed under vacuum conditions. The speed of dry ball milling was 200 rpm and the time of dry ball milling was 6 h. After dry ball milling, mixed powder A was obtained; (2) In an argon atmosphere, the mixed powder A is placed in a tube furnace for sintering, and after the sintering is completed, the mixed powder B is obtained; (3) Putting the mixed powder B into a hydrothermal reactor, adding 2,5-diphenyl-1,4-benzoquinone and ethanol, and carrying out a hydrothermal reaction; (4) The material obtained after the hydrothermal reaction is placed in a vacuum drying oven for drying, and after drying, a multidimensional conductive network sodium ion battery negative electrode material is obtained.

2. The method for preparing the multidimensional conductive network sodium ion battery negative electrode material according to claim 1, characterized in that: In the step (1), the mass ratio of red phosphorus to MnSn2 is 10:(1-2).

3. The method for preparing the multidimensional conductive network sodium ion battery negative electrode material according to claim 1, characterized in that: In the step (1), the ball-to-material ratio of dry ball milling is (8-10):

1.

4. The method for preparing the multidimensional conductive network sodium ion battery negative electrode material according to claim 1, characterized in that: In the step (2), the sintering temperature is 350-400°C, the sintering time is 8-10h, and the heating rate is 1-3°C / min.

5. The method for preparing the multidimensional conductive network sodium ion battery negative electrode material according to claim 1, characterized in that: In the step (3), the mass ratio of the mixed powder B to 2,5-diphenyl-1,4-benzoquinone is 40:(1-2).

6. The method for preparing the multidimensional conductive network sodium ion battery negative electrode material according to claim 1, characterized in that: In the step (3), the mass volume ratio of the total amount of the mixed powder B and 2,5-diphenyl-1,4-benzoquinone added to the amount of ethanol added is (4-6): 20 mg / mL.

7. The method for preparing the multidimensional conductive network sodium ion battery negative electrode material according to claim 1, characterized in that: In the step (3), the temperature of the hydrothermal reaction is 450-500°C, the time of the hydrothermal reaction is 3-5h, and the heating rate is 1-3°C / min.

8. The method for preparing the multi-dimensional conductive network sodium ion battery negative electrode material according to claim 1, characterized in that: In the step (4), the drying temperature is 90-120° C. and the drying time is 8-12 hours.

9. A multidimensional conductive network sodium ion battery negative electrode material, characterized in that: The negative electrode material of a multi-dimensional conductive network sodium ion battery is prepared by the method for preparing the negative electrode material of a multi-dimensional conductive network sodium ion battery according to any one of claims 1 to 8.

10. An application of the multi-dimensional conductive network sodium ion battery negative electrode material according to claim 9, characterized in that: Used in the preparation of sodium ion batteries.

Citation Information

Patent Citations

  • Metal phosphide used as lithium ion secondary battery cathode material and preparation method thereof

    CN101556998A

  • Stannic phosphide / graphene composite cathode material for sodium-ion battery and preparation method thereof

    CN105006551A